2014
DOI: 10.1590/s1516-89132014000100015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fatty acid content of fresh and frozen fillets of rainbow trout (Oncorhynchus mykiss) Walbaum

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
4
11
0
Order By: Relevance
“…Other predominant SFAs were stearic acid in both species. Similar results also obtained from for S. trutta macrostigma (Akpinar, Görgün, & Akpinar, 2009;Ateş et al, 2013;Haliloğlu, Bayir, Sirkecioğlu, & Aras, 2005) and O. mykiss (Chávez-Mendoza et al, 2014;Kalyoncu, Yaman, & Aktumsek, 2010;Sabetian, Delshad, Moini, Islami, & Motalebi, 2012). Kaya & Erdem (2009) also reported that palmitic and stearic acid were major SFA in wild and farmed trout.…”
Section: Resultssupporting
confidence: 75%
“…Other predominant SFAs were stearic acid in both species. Similar results also obtained from for S. trutta macrostigma (Akpinar, Görgün, & Akpinar, 2009;Ateş et al, 2013;Haliloğlu, Bayir, Sirkecioğlu, & Aras, 2005) and O. mykiss (Chávez-Mendoza et al, 2014;Kalyoncu, Yaman, & Aktumsek, 2010;Sabetian, Delshad, Moini, Islami, & Motalebi, 2012). Kaya & Erdem (2009) also reported that palmitic and stearic acid were major SFA in wild and farmed trout.…”
Section: Resultssupporting
confidence: 75%
“…Different studies reported that values of IA and IT, the meat‐lipid quality parameters, should not be more than 1.00 for human health (Chávez‐Mendoza et al ; Łuczynska, Paszczyk, Nowosad, & Łuczynski, ) and high H/H ratio in fish meat is considered to be more beneficial for human health (Fernandes et al, ). In this study, fish meat IA and IT values were lower than 1.00 and H/H ratios were high in both the beginning and end of the study and these values were sufficient for human health according to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Chávez‐Mendoza et al. [ 53 ] reported the total saturated fat amounts (ΣSFA) in fresh trout fillets as 24.67% and after frozen storage of days 45 and 90 as 32.87% and 32.72%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the results of this study, many researchers reported that trout contained oleic acid which is dominant fatty acids among MUFAs. [ 53,54 ]…”
Section: Resultsmentioning
confidence: 99%